Environmental Health Literacy and The Hope Tree Metaphor - Dessyka Febria; Milda Hastuty; Rama Agustina; Yusnilasari; Deby Utami Siska Ariani (Postgraduate, University of Mataram, 2023)
This research aim to develop the concept of EHL by reflecting the wish tree metaphor in supporting interactions between government, communities, companies, and agencies to achieve the vision of environmental health. This research used a qualitative methodology with a phenomenological perspective. The community, the penghulu, the village secretary, the village midwife, as well as businesses, professionals, and peatlands specialists served as the study's informants. The peatlands where the study is being conducted is in Indonesia's Riau Province's Rokan Hilir Regency. As a result of this research, it is hoped that stakeholders will become more knowledgeable about the detrimental effects of peatlands management and that they will be able to lessen the negative effects of poor community sanitation on peatlands, protecting the environment and lowering health risks. This metaphor of the wishing tree is said to be upbeat and holding on to improvements in the quality of life in the future. This research is a reflection study that results in a wish tree metaphor that expresses the desire that stakeholders would adopt EHL successfully.